2016
DOI: 10.1016/j.apcata.2016.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the properties of BaTi0.8Cu0.2O3 catalyst selecting the synthesis method

Abstract: Highlights-BaTiO3 and BaTi0.8Cu0.2O3 perovskites were synthesized using sol-gel and hydrothermal methods.-The location of copper in the catalyst depends on the synthesis method.-Cu-BTOsg, with Cu incorporated into the structure, presents a high NOx storage capacity.-Cu-BBOH, with CuO highly dispersed on the surface, shows a high activity for NO to NO2 oxidation. This is a previous version of the article published in Applied Catalysis A: General. 2016General. , 519: 7-15. doi:10.1016General. /j.apcata.2016 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(62 citation statements)
references
References 58 publications
(78 reference statements)
12
50
0
Order By: Relevance
“…In previous studies [11,12], titanium was partially substituted by copper in the BaTiO 3 perovskite structure, showing the resulting BaTi 1−x Cu x O 3 perovskites a high activity for NOx storage, which was attributed to the presence of oxygen vacancies (created on the catalyst surface as a consequence of the copper incorporation into the structure) and to the segregation of some phases (mainly BaCO 3 and Ba 2 TiO 4 , but also CuO). It was also concluded that the BaTi 0.8 Cu 0.2 O 3 catalyst presents a NOx storage capacity (NSC) at 420 • C in the range of levels reported for noble metal-based catalysts (around 300 µmol/g) [13], and hence could be proposed as a potential component of high-temperature LNT systems for lean burn engines, such as gasoline direct injection engines.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…In previous studies [11,12], titanium was partially substituted by copper in the BaTiO 3 perovskite structure, showing the resulting BaTi 1−x Cu x O 3 perovskites a high activity for NOx storage, which was attributed to the presence of oxygen vacancies (created on the catalyst surface as a consequence of the copper incorporation into the structure) and to the segregation of some phases (mainly BaCO 3 and Ba 2 TiO 4 , but also CuO). It was also concluded that the BaTi 0.8 Cu 0.2 O 3 catalyst presents a NOx storage capacity (NSC) at 420 • C in the range of levels reported for noble metal-based catalysts (around 300 µmol/g) [13], and hence could be proposed as a potential component of high-temperature LNT systems for lean burn engines, such as gasoline direct injection engines.…”
Section: Introductionmentioning
confidence: 93%
“…In fact, an interesting challenge has been highlighted in a recent EU report, regarding the need to develop alternatives to the use of critical raw materials such as precious metals [9]. In this line, the potential of perovskite base catalysts is being largely illustrated in the literature for environmental applications [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations